Virological and genetic characteristics of human respiratory syncytial viruses isolated in Russia, 2017-2018 - Elena Alexandrovna Prokopyeva; Olga Grigoryevna Kurskaya; Mariya Vladimirovna Solomatina; Ivan Andreevich Sobolev; Tereza Araevna Saroyan; Nikita Artemyevich Dubovitskiy; Anastasiya Alexandrovna Derko; Peter Mikchailovich Kozhin; Tatyana Yurievna Alikina; Marsel Rasimovich Kabilov; Alexander Mikchailovich Shestopalov; Kirill Alexandrovich Sharshov (Journal of Infection in Developing Countries)
Isolation of human respiratory syncytial virus (HRSV) from clinical samples and storage of isolates for long period remains a considerable problem. We describe in detail the optimized conditions of HRSV isolation and cultivation in three cell cultures HeLa, HEp-2, and Vero. HRSV was detected in 35.2% (166/471) specimens by real-time PCR from symptomatic infants and children up to 15 years from October 2017 to March 2018 in Russia. HRSV-positive samples were used for virus isolation in HeLa, HEp-2, and Vero cells in different manners (in monolayer or suspension). To optimize the conditions of HRSV cultivation, these cell cultures were treated or not with receptor-destroying enzyme (RDE). Ten isolates were successfully obtained by the way of infection of the suspension of cells with subsequent RDE treatment. Among them, several isolates induced the cytopathogenic effect (CPE) by the syncytium formation in both Hela and HEp-2 cell cultures. The genetic analysis revealed that the manners of isolation by using monolayer or suspension and subsequent RDE treatment did not influence the nucleotide and amino acid structures of obtained HRSVs. The CPE characteristics of obtained viruses were the same in HeLa, HEp-2, and Vero cell cultures, and were described as large syncytium up to 150 microns or more in size with the nuclei peripheral location and an optically bright zone in the center of the formation. We showed that infection of cell suspension with the subsequent RDE treatment increased the chance of HRSVs isolation from clinical samples.